Modified Pt / ZSM-23 catalyst, preparation method and application thereof
By optimizing the synthesis and modification process of ZSM-23 molecular sieve, a modified Pt/ZSM-23 catalyst was prepared, which solved the problem of low hydroisomerization activity and selectivity of Fischer-Tropsch wax, and achieved efficient preparation of high viscosity index, The effect of low pour point base oil.
Patent Information
- Application Number
- CN202310218458.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-07
AI Technical Summary
In the prior art, Fischer-Tropsch wax hydroisomer catalyst has low reactivity and selectivity, making it difficult to effectively prepare high viscosity index and low pour point lubricating oil base oil.
ZSM-23 molecular sieve was synthesized by DMF template agent, molded by ammonium exchange and alumina mixing, loaded with Pt metal, and finally added organic amine to the catalyst for modification, optimize the pore structure and acidity of the catalyst, and prepare the modification by equal volume impregnation method. Pt/ZSM-23 catalyst.
It significantly improves the specific selectivity and reactivity of the catalyst to Fischer-Tropsch wax raw materials, improves the mass transfer of materials, improves the conversion rate of heavy linear hydrocarbons and base oil yield, and prepares high viscosity index and low pour point base oil. .
Smart Images

Figure CN116116456B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieve catalysts, and in particular to a modified Pt / ZSM-23 catalyst, a preparation method and application thereof. Background Art
[0002] The isomerization reaction of long straight-chain alkanes is mainly carried out on bifunctional molecular sieve catalysts. The acidic sites of the molecular sieve carrier provide isomerization function, and the active metal sites provide hydrogenation / dehydrogenation function. One-dimensional straight pore molecular sieves, such as SAPO-11, ZSM-22, ZSM-23, and ZSM-48, have broad application prospects as isomerization catalyst carriers due to their special pore structure and acidity. ZSM-23 molecular sieve has a unique one-dimensional ten-membered ring straight pore and an MTT-type topological structure, and is widely used in the preparation of lubricating oil hydroisomerization decondensation catalyst materials.
[0003] Patent US4076842 uses pyrrolidine as a template to synthesize ZSM-23 molecular sieve. Patents US4490342, US5405596, and CN10214971A disclose methods for synthesizing ZSM-23 molecular sieves using NN-trimethylheptamine, NN-trimethyldodecylamine, and isopropylamine as templates, respectively. However, when the ZSM-23 molecular sieve catalyst synthesized using the prior art is used to produce high viscosity index and low pour point lubricating oil base oil using Fischer-Tropsch wax as a raw material, the reaction activity and selectivity are not high. Summary of the invention
[0004] The main purpose of the present invention is to provide a modified Pt / ZSM-23 catalyst, a preparation method and application thereof, so as to solve the problem of low reaction activity and selectivity of Fischer-Tropsch wax hydroisomerization catalyst in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing a modified Pt / ZSM-23 catalyst is provided, comprising the following steps: step S1, mixing a silicon source, an aluminum source, sodium hydroxide, a DMF template, a seed and water to obtain a sol; crystallizing the sol, and then performing a first calcination to obtain a Na-type ZSM-23 molecular sieve; step S2, exchanging the Na-type ZSM-23 molecular sieve with an ammonium salt aqueous solution, and then performing a second calcination to obtain an H-type ZSM-23 molecular sieve; step S3, mixing the H-type ZSM-23 molecular sieve with alumina, adding nitric acid for kneading, extruding into strips, and then performing a third calcination to obtain a ZSM-23 catalyst carrier; step S4, impregnating the ZSM-23 catalyst carrier in a Pt salt aqueous solution, and then performing a fourth calcination to obtain a Pt / ZSM-23 catalyst; step S5, adding an organic amine and water to the Pt / ZSM-23 catalyst for modification, and then performing a fifth calcination to obtain a modified Pt / ZSM-23 catalyst.
[0006] Furthermore, in step S1, the silicon-aluminum ratio is (80-200):1; the mold-silicon ratio is (0.5-0.8):1, the alkali-silicon ratio is (0.07-0.9):1, the water-silicon ratio is (20-50):1, and the crystalline-silicon ratio is (0.02-0.1):1; preferably, the aluminum source is Al2(SO4)3·18H2O, the silicon source is silica sol, and the seed crystal is ZSM-23.
[0007] Furthermore, in step S1, the crystallization temperature is 140-180°C, and the time is 24-150 hours; preferably, the first calcination temperature is 450-600°C, and the time is 4-10 hours.
[0008] Furthermore, in step S2, the ammonium salt aqueous solution is an ammonium chloride aqueous solution; preferably, the mass concentration of the ammonium salt aqueous solution is 0.2-0.8 mol / L; more preferably, the temperature of ammonium exchange is 50-90°C, the number of times is 2-4 times, and the time of each exchange is 0.5-2h; further preferably, the temperature of the second roasting is 500-600°C, and the time is 8-16h.
[0009] Furthermore, in step S3, the mass ratio of H-type ZSM-23 molecular sieve to alumina is (6-8):3, and the amount of nitric acid added is 1-5% of the total mass of H-type ZSM-23 molecular sieve and alumina; preferably, the temperature of the third calcination is 500-600°C, and the time is 8-16h.
[0010] Furthermore, in step S4, the Pt metal loading in the Pt / ZSM-23 catalyst is 0.2-0.6%; preferably, the temperature of the fourth calcination is 350-450° C., and the time is 1-5 h.
[0011] Furthermore, in step S5, the organic amine is n-butylamine; preferably, per gram of Pt / ZSM-23 catalyst, the amount of water added is 5 to 20 g, and the amount of the organic amine added is 5 to 15 mmol.
[0012] Furthermore, in step S5, the temperature of the modification process is 150-200°C, and the time is 15-30 hours; preferably, the temperature of the fifth calcination is 450-550°C, and the time is 5-10 hours.
[0013] According to another aspect of the present invention, there is provided a modified Pt / ZSM-23 catalyst obtained by the preparation method of the present invention.
[0014] According to another aspect of the present invention, there is provided a use of the modified Pt / ZSM-23 catalyst in the hydroisomerization of Fischer-Tropsch wax.
[0015] By applying the technical solution of the present invention, a DMF template is used, and a ZSM-23 molecular sieve with special pores and acidity is prepared by optimizing the catalyst formula and the synthesis path. Then, a bifunctional Pt / ZSM-23 catalyst is prepared by an equal volume impregnation method, and the catalyst is modified by an organic amine, thereby further increasing its specific selectivity for Fischer-Tropsch wax raw materials. The preparation method of the present invention is simple and low in cost. The prepared modified catalyst has excellent isomerization performance and is particularly suitable for the hydrogenation isomerization reaction of Fischer-Tropsch wax raw materials, so that the mass transfer of materials during the reaction process is improved, and heavy straight-chain alkanes are effectively converted, thereby preparing a high viscosity index and low pour point base oil. The modified catalyst of the present invention has high reaction activity and selectivity, and can significantly improve the base oil yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The XRD pattern of the ZSM-23 molecular sieve catalyst support according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0019] Terminology explanation:
[0020] Silicon-aluminum ratio: the molar ratio of SiO2 to Al2O3.
[0021] Template-silicon ratio: the molar ratio of template to SiO2.
[0022] Alkali-silicon ratio: the molar ratio of sodium hydroxide to SiO2.
[0023] Water-silicon ratio: the molar ratio of water to SiO2.
[0024] Crystal-silicon ratio: the ratio of the mass of the seed crystal to the mass of SiO2.
[0025] As described in the background of the present invention, the prior art has the problem of low reaction activity and selectivity of Fischer-Tropsch wax hydroisomerization catalyst. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a modified Pt / ZSM-23 catalyst is provided, comprising the following steps: step S1, mixing a silicon source, an aluminum source, sodium hydroxide, a DMF template, a seed crystal and water to obtain a uniform sol; crystallizing the sol, and then performing a first calcination to obtain a Na-type ZSM-23 molecular sieve; step S2, exchanging the Na-type ZSM-23 molecular sieve with an ammonium salt aqueous solution, and then performing a second calcination to obtain an H-type ZSM-23 Molecular sieve; step S3, mixing H-type ZSM-23 molecular sieve with alumina, adding nitric acid for kneading, extruding into strips, and then performing a third calcination to obtain a ZSM-23 catalyst carrier; step S4, impregnating the ZSM-23 catalyst carrier in a Pt salt water solution, and then performing a fourth calcination to obtain a Pt / ZSM-23 catalyst; step S5, adding an organic amine and water to the Pt / ZSM-23 catalyst for modification, and then performing a fifth calcination to obtain a modified Pt / ZSM-23 catalyst.
[0026] The invention firstly mixes a silicon source, an aluminum source, sodium hydroxide, a DMF template agent, a seed crystal and water to obtain a sol for crystallization. After the crystallization is completed, the temperature is rapidly lowered, and the template agent is removed through suction filtration, washing, drying and a first calcination. By adopting the DMF template agent and optimizing the catalyst formula and the synthesis path, a Na-type ZSM-23 molecular sieve with special pores and acidity is prepared. Subsequently, the Na-type ZSM-23 molecular sieve is ammonium exchanged with an ammonium salt aqueous solution so that the sodium ions on the molecular sieve are replaced by ammonium ions. After the ammonium exchange is completed, filtration, washing, drying and a second calcination are performed to obtain an H-type ZSM-23 molecular sieve. Then, the H-type ZSM- The ZSM-23 molecular sieve is mixed with alumina, nitric acid is added for kneading, extruded into strips, and then calcined for the third time to obtain a ZSM-23 catalyst carrier, which is impregnated in a Pt salt solution to load Pt, and calcined for the fourth time, and a bifunctional Pt / ZSM-23 catalyst is prepared by an equal volume impregnation method; finally, organic amines and water are added to the Pt / ZSM-23 catalyst, and their alkalinity is utilized to further improve the acid content and acid distribution of the molecular sieve, thereby modifying the molecular sieve, and then cooled, filtered, washed, dried and calcined for the fifth time to further increase its specific selectivity for the Fischer-Tropsch wax raw material, thereby obtaining a modified Pt / ZSM-23 catalyst.
[0027] The modified catalyst prepared by the present invention has a more suitable pore size and a unique pore structure, which can better limit the generation of multi-branched alkanes, thereby reducing the progress of cracking reactions and improving the selectivity of the catalyst to single-branched alkanes; at the same time, the carbon deposition rate can be further reduced and the service life of the catalyst can be extended. The modified catalyst prepared by the present invention has excellent isomerization performance, and is particularly suitable for the hydrogenation isomerization reaction of Fischer-Tropsch wax feedstock, so that the mass transfer of materials during the reaction process is improved, and heavy straight-chain alkanes are effectively converted, thereby preparing a high viscosity index and low pour point base oil. The modified catalyst of the present invention has high reaction activity and selectivity, and can significantly improve the base oil yield.
[0028] The raw material ratio will affect the synthesis of ZSM-23 molecular sieve, and the seed amount will affect the crystallinity and crystallization kinetics of the synthesized molecular sieve. In a preferred embodiment, in step S1, the silicon-aluminum ratio is (80-200):1; the mold silicon ratio is (0.5-0.8):1, the alkali silicon ratio is (0.07-0.9):1, the water silicon ratio is (20-50):1, and the crystal silicon ratio is (0.02-0.1):1. The above range is the optimal synthetic phase region, which is more conducive to the formation of high-purity and high-crystallinity Na-type ZSM-23 molecular sieve, further improving the pore structure and acidity of the molecular sieve, so that it has a larger micropore specific surface area and pore volume, thereby further increasing the reaction activity and selectivity of the catalyst.
[0029] The silicon source and the aluminum source can be the commonly used raw materials in the art. Preferably, the aluminum source is Al2(SO4)3·18H2O, the silicon source is silica sol, and the seed crystal is ZSM-23. The above raw materials are more suitable for the formation of the molecular sieve of the present invention and the performance of catalytic performance.
[0030] In a preferred embodiment, in step S1, the crystallization temperature is 140-180°C and the time is 24-150 hours, and a more uniform ZSM-23 molecular sieve primary structural unit can be obtained; preferably, the first calcination temperature is 450-600°C and the time is 4-10 hours, which can more fully remove the template agent and is more conducive to the formation of a special pore structure of the molecular sieve, thereby improving the catalytic performance.
[0031] To further improve the effect of ammonium exchange, in a preferred embodiment, in step S2, the ammonium salt aqueous solution is an ammonium chloride aqueous solution; preferably, the mass concentration of the ammonium salt aqueous solution is 0.2-0.8 mol / L; more preferably, the temperature of ammonium exchange is 50-90°C, the number of times is 2-4 times, and the time of each exchange is 0.5-2h. Under the above conditions, the ammonium exchange efficiency is better; further preferably, the temperature of the second calcination is 500-600°C, and the time is 8-16h, which can more fully convert the ammonium type molecular sieve into the hydrogen type molecular sieve.
[0032] In a preferred embodiment, in step S3, the mass ratio of H-type ZSM-23 molecular sieve to alumina is (6-8):3, and the amount of nitric acid added is 1-5% of the total mass of the H-type ZSM-23 molecular sieve and alumina, which is more convenient for the molding process of the catalyst carrier; preferably, the temperature of the third calcination is 500-600°C and the time is 8-16h. Under the above conditions, the catalyst carrier can be molded more quickly and completely.
[0033] In order to ensure that the catalyst carrier is loaded with a sufficient amount of active metal catalyst without causing waste of raw materials, in a preferred embodiment, in step S4, the Pt metal loading in the Pt / ZSM-23 catalyst is 0.2-0.6%; preferably, the temperature of the fourth calcination is 350-450°C, and the time is 1-5h, so that Pt can be loaded more evenly on the catalyst carrier.
[0034] In a preferred embodiment, in step S5, the organic amine is n-butylamine, which has a more suitable alkalinity; preferably, per gram of Pt / ZSM-23 catalyst, the amount of water added is 5 to 20 g, and the amount of the organic amine added is 5 to 15 mmol, which can further improve the acid content and acid distribution of the catalyst.
[0035] In a preferred embodiment, in step S5, the modification temperature is 150-200°C and the time is 15-30 hours, which can further improve the catalyst acid content and acid distribution. Preferably, the fifth calcination temperature is 450-550°C and the time is 5-10 hours, which can further improve the catalyst stability.
[0036] In another typical embodiment of the present invention, a modified Pt / ZSM-23 catalyst is provided, which is obtained by the preparation method of the present invention and has excellent reaction activity, selectivity and isomerization performance.
[0037] In another typical embodiment of the present invention, there is also provided the use of the modified Pt / ZSM-23 catalyst in the hydroisomerization of Fischer-Tropsch wax, which has excellent isomerization performance, high reaction activity and selectivity, can improve the mass transfer of materials during the hydroisomerization reaction of Fischer-Tropsch wax feedstock, and effectively convert heavy straight-chain alkanes, thereby preparing a base oil with a high viscosity index and a low pour point, and can significantly improve the base oil yield.
[0038] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0039] Example 1
[0040] (1) Weigh 9.24 g of Al2(SO4)3·18H2O and dissolve it in 240 g of water, add 100.8 g of DMF, mix and stir evenly to form a mixture A. Weigh 62.4 g of NaOH and dissolve it in 1080 g of water, add dropwise 410.4 g of silica sol, add 6.6 g of ZSM-23 seed crystals, mix and stir evenly to form a mixture B. Add mixture A to mixture B, mix and stir evenly to form a sol system, the molar ratio of each raw material is: SiO2 / Al2O3=147, DMF / SiO2=0.67, NaOH / SiO2=0.76, H2O / SiO2=43, and the seed crystal is 5% of the mass of SiO2. Transfer the sol into a crystallization kettle, the crystallization temperature is 170°C, and the crystallization time is 46 hours. After the crystallization, the temperature was rapidly lowered, filtered, washed, and dried at 120°C for 6 hours to obtain a sodium-type molecular sieve containing a template, which was then calcined at 550°C for 5 hours to obtain a Na-ZSM-23 molecular sieve.
[0041] (2) Weigh 100g of molecular sieve and put it into 1L of 0.6mol / L ammonium chloride solution for ammonium exchange at 85℃ for 2 hours, filter and wash, repeat this condition for 3 times. After the exchange, dry at 120℃ for 8 hours and calcine at 550℃ for 10 hours to obtain H-ZSM-23 molecular sieve.
[0042] (3) Weigh 100 g of H-ZSM-23 molecular sieve and 55 g of SB powder (alumina powder, dry basis content 78%), mix them evenly with the H-ZSM-23 molecular sieve, prepare 93 g of 3.3% nitric acid solution, slowly drop the nitric acid solution into the molecular sieve powder, knead and extrude into strips, dry at 120° C. for 8 hours, and calcine at 550° C. for 10 hours to obtain a ZSM-23 molecular sieve catalyst carrier. The XRD pattern is shown in FIG. Figure 1 .
[0043] (4) Weigh 100 g of the above-mentioned carrier, prepare 78 g of 0.45% Pt(NH4)4Cl2 by mass, use saturated water absorption for impregnation, dry naturally, and calcine at 400°C for 3 hours to obtain a Pt / ZSM-23 catalyst.
[0044] (5) Weigh 100 g of Pt / ZSM-23 catalyst, 500 g of water, and 36.5 g of n-butylamine, mix well, and transfer to a crystallization kettle for modification. The modification temperature is 150° C. and the time is 15 hours. The modified catalyst is cooled, filtered, washed, dried at 120° C. for 6 hours, and calcined at 500° C. for 8 hours to obtain an organic amine-modified Pt / ZSM-23 catalyst.
[0045] Example 2
[0046] (1) Weigh 8.06 g of Al2(SO4)3·18H2O and dissolve it in 240 g of water, add 95.8 g of DMF, mix and stir evenly to form a mixture A. Weigh 59.9 g of NaOH and dissolve it in 1080 g of water, add dropwise 410.4 g of silica sol, add 10.5 g of ZSM-23 seed crystals, mix and stir evenly to form a mixture B. Add mixture A to mixture B, mix and stir evenly to form a sol system, the molar ratio of each raw material is: SiO2 / Al2O3=169, DMF / SiO2=0.64, NaOH / SiO2=0.73, H2O / SiO2=43, and the seed crystal is 8% of the mass of SiO2. Transfer the sol into a crystallization kettle, the crystallization temperature is 170°C, and the crystallization time is 37 hours. After the crystallization, the temperature was rapidly lowered, filtered, washed, and dried at 120°C for 6 hours to obtain a sodium-type molecular sieve containing a template, which was then calcined at 550°C for 5 hours to obtain a Na-ZSM-23 molecular sieve.
[0047] (2) Weigh 100g of Na-ZSM-23 molecular sieve and put it into 1L of 0.6mol / L ammonium chloride solution for ammonium exchange at 85°C for 2 hours, filter and wash, repeat this condition for 3 times. After the exchange, dry at 120°C for 8 hours and calcine at 550°C for 10 hours to obtain H-ZSM-23 molecular sieve.
[0048] (3) Weigh 100 g of H-ZSM-23 molecular sieve and 55 g of SB powder (dry basis content 78%), mix them evenly with the molecular sieve, prepare 93 g of 3.3% nitric acid solution by mass, slowly add the nitric acid solution dropwise to the molecular sieve powder, knead and extrude into strips, dry at 120° C. for 8 hours, and calcine at 550° C. for 10 hours to obtain a catalyst carrier.
[0049] (4) Weigh 100 g of the above-mentioned carrier, prepare 78 g of 0.45% Pt(NH4)4Cl2 by mass, use saturated water absorption for impregnation, dry naturally, and calcine at 400°C for 3 hours to obtain a Pt / ZSM-23 catalyst.
[0050] (5) Weigh 100 g of Pt / ZSM-23 catalyst, 2000 g of water, and 109.5 g of n-butylamine, mix well, and transfer to a crystallization kettle for modification. The modification temperature is 200° C. and the time is 30 hours. The modified catalyst is cooled, filtered, washed, dried at 120° C. for 6 hours, and calcined at 500° C. for 8 hours to obtain an organic amine-modified Pt / ZSM-23 catalyst.
[0051] Example 3
[0052] (1) Weigh 10.11 g Al2(SO4)3·18H2O and dissolve it in 240 g water, add 107.8 g DMF, mix and stir evenly to form mixture A. Weigh 65.6 g NaOH and dissolve it in 1080 g water, add dropwise 410.4 g silica sol, add 3.9 g ZSM-23 seed crystals and mix and stir evenly to form mixture B. Add mixture A to mixture B, mix and stir evenly to form a sol system, the molar ratio of each raw material is: SiO2 / Al2O3=147, DMF / SiO2=0.72, NaOH / SiO2=0.80, H2O / SiO2=43, and the seed crystal is 3% of the mass of SiO2. Transfer the sol into a crystallization kettle, the crystallization temperature is 170°C, and the crystallization time is 42 hours. After the crystallization is completed, cool rapidly, filter, wash, and dry at 120°C for 6 hours to obtain a template-containing sodium molecular sieve. Na-ZSM-23 molecular sieve was obtained after calcination at 550°C for 5h.
[0053] (2) Weigh 100g of Na-ZSM-23 and put it into 1L of 0.6mol / L ammonium chloride solution for ammonium exchange at 85°C for 2 hours, filter and wash, repeat this condition for 3 times. After the exchange, dry at 120°C for 8 hours and calcine at 550°C for 10 hours to obtain H-ZSM-23 molecular sieve.
[0054] (3) Weigh 100 g of H-ZSM-23 molecular sieve and 55 g of SB powder (dry basis content 78%), mix them evenly with the molecular sieve, prepare 93 g of 3.3% nitric acid solution by mass, slowly add the nitric acid solution dropwise to the molecular sieve powder, knead and extrude into strips, dry at 120° C. for 8 hours, and calcine at 550° C. for 10 hours to obtain a catalyst carrier.
[0055] (4) Weigh 100 g of the above-mentioned carrier, prepare 78 g of 0.45% Pt(NH4)4Cl2 by mass, use saturated water absorption for impregnation, dry naturally, and calcine at 400°C for 3 hours to obtain a Pt / ZSM-23 catalyst.
[0056] (5) Weigh 100 g of Pt / ZSM-23 catalyst, 750 g of water, and 73 g of n-butylamine, mix well, and transfer to a crystallization kettle for modification. The modification temperature is 175°C and the time is 23 hours. The modified catalyst is cooled, filtered, washed, dried at 120°C for 6 hours, and calcined at 500°C for 8 hours to obtain an organic amine-modified Pt / ZSM-23 catalyst.
[0057] Example 4
[0058] (1) Prepare a sol system according to Example 1, with the molar ratio of each raw material being: SiO2 / Al2O3=80, DMF / SiO2=0.5, NaOH / SiO2=0.07, H2O / SiO2=20, and the seed crystal being 2% of the mass of SiO2. Transfer the sol into a crystallization kettle, with a crystallization temperature of 140°C and a crystallization time of 150 hours. After the crystallization is completed, cool rapidly, filter, wash, and dry at 120°C for 6 hours to obtain a sodium-type molecular sieve containing a template, which is then calcined at 450°C for 10 hours to obtain a Na-ZSM-23 molecular sieve.
[0059] (2) Weigh 100 g of molecular sieve and put it into 1 L of 0.2 mol / L ammonium chloride solution for ammonium exchange at 50°C for 2 hours, filter and wash, repeat this condition for 4 times. After the exchange, dry at 120°C for 8 hours and calcine at 500°C for 16 hours to obtain H-ZSM-23 molecular sieve.
[0060] (3) Weigh 100 g of H-ZSM-23 molecular sieve and 48 g of SB powder (alumina powder, dry basis content 78%), mix well with the H-ZSM-23 molecular sieve, prepare 41.6 g of 3.3% nitric acid solution by mass, slowly add the nitric acid solution dropwise to the molecular sieve powder, knead and extrude into strips, dry at 120° C. for 8 hours, and calcine at 500° C. for 16 hours to obtain a ZSM-23 molecular sieve catalyst carrier.
[0061] (4) Weigh 100 g of the above-mentioned carrier, prepare 133 g of 0.45% Pt(NH4)4Cl2 by mass, use saturated water absorption for impregnation, dry naturally, and calcine at 350°C for 5 hours to obtain a Pt / ZSM-23 catalyst.
[0062] (5) Weigh 100 g of Pt / ZSM-23 catalyst, 500 g of water, and 36.5 g of n-butylamine, mix well, and transfer to a crystallization kettle for modification. The modification temperature is 150° C. and the time is 30 hours. The modified catalyst is cooled, filtered, washed, dried at 120° C. for 6 hours, and calcined at 450° C. for 10 hours to obtain an organic amine-modified Pt / ZSM-23 catalyst.
[0063] Example 5
[0064] (1) Prepare a sol system according to Example 1, with the molar ratio of each raw material being: SiO2 / Al2O3=200, DMF / SiO2=0.8, NaOH / SiO2=0.9, H2O / SiO2=50, and the seed crystal being 10% of the mass of SiO2. Transfer the sol into a crystallization kettle, with a crystallization temperature of 180°C and a crystallization time of 24 hours. After the crystallization is completed, cool rapidly, filter, wash, and dry at 120°C for 6 hours to obtain a sodium-type molecular sieve containing a template, which is then calcined at 600°C for 4 hours to obtain a Na-ZSM-23 molecular sieve.
[0065] (2) Weigh 100 g of molecular sieve and put it into 1 L of 0.8 mol / L ammonium chloride solution for ammonium exchange at 90°C for 0.5 hour, filter and wash, repeat this condition for ammonium exchange twice. After the exchange, dry at 120°C for 8 hours and calcine at 600°C for 8 hours to obtain H-ZSM-23 molecular sieve.
[0066] (3) Weigh 100 g of H-ZSM-23 molecular sieve and 64 g of SB powder (alumina powder, dry basis content 78%), mix them evenly with the H-ZSM-23 molecular sieve, prepare 227 g of 3.3% nitric acid solution by mass, slowly add the nitric acid solution dropwise to the molecular sieve powder, knead and extrude into strips, dry at 120° C. for 8 hours, and calcine at 600° C. for 8 hours to obtain a ZSM-23 molecular sieve catalyst carrier.
[0067] (4) Weigh 100 g of the above-mentioned carrier, prepare 44 g of 0.45% Pt(NH4)4Cl2, use saturated water absorption impregnation, dry naturally, and calcine at 450°C for 1 hour to obtain a Pt / ZSM-23 catalyst.
[0068] (5) Weigh 100 g of Pt / ZSM-23 catalyst, 2000 g of water, and 109.5 g of n-butylamine, mix well, and transfer to a crystallization kettle for modification. The modification temperature is 200° C. and the time is 15 hours. The modified catalyst is cooled, filtered, washed, dried at 120° C. for 6 hours, and calcined at 550° C. for 5 hours to obtain an organic amine-modified Pt / ZSM-23 catalyst.
[0069] Comparative Example 1
[0070] The difference between Comparative Example 1 and Example 3 is that in step (1), silica sol, aluminum sulfate, sodium hydroxide, pyrrolidine template agent, and water are mixed uniformly in a certain proportion to form a sol system, and stirred uniformly, and the molar ratio of each material is: SiO2 / Al2O3=120, template agent / SiO2=0.53, NaOH / SiO2=0.08, H2O / SiO2=35. The sol is transferred to a crystallization kettle for subsequent preparation.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 1 is that in step (5), 100 g of Pt / ZSM-23 catalyst, 750 g of water, and 20 g of n-butylamine are weighed, mixed evenly, and transferred into a crystallization kettle for subsequent modification.
[0073] Comparative Example 3
[0074] Take 100g of sodium ZSM-23 molecular sieve containing isopropylamine template, place it in 3L of NaOH solution with a concentration of 0.2mol / L, treat it at 80℃ for 180min, filter, wash until the eluent is neutral, dry and calcine to remove the template; the resulting product is placed in 2L of NH4NO3 solution with a concentration of 0.5mol / L, exchange for 180min at 60℃, filter, wash with deionized water until the eluent is neutral, exchange continuously (repeat the above operation) twice, dry at 120℃, and calcine at 550℃ for 24h to obtain hydrogen ZSM-23 molecular sieve (H-ZSM-23). 30g of alumina (γ-Al2O3) was mixed evenly with it, and 80g of 5wt.% HNO3 solution was added, kneaded at room temperature for 2h, extruded at room temperature using an automatic extruder, dried naturally, and then dried at 120°C for 4h, and calcined at 550°C for 8h to obtain a molecular sieve carrier H-ZSM-23 carrier). 100g of the above carrier was impregnated with 10mL of chloroplatinic acid (H2PtCl6) solution containing 0.05g / mL platinum (Pt) solution to obtain a 0.5wt.% Pt / H-ZSM-23 catalyst.
[0075] Comparative Example 4
[0076] 0.46 g of aluminum sulfate 18hydrate was quickly added dropwise to 6.32 mL of an aqueous solution containing DMF, wherein the volume ratio of DMF to water was 1.14, and stirred for 1 h to form liquid A; 14.44 g of tetraethyl orthosilicate was slowly added dropwise to an aqueous solution of NaOH (2.05 g of NaOH was added to 43.36 g of water), wherein the mass ratio of sodium hydroxide to water was 0.05, to form liquid B; liquid A was added dropwise to liquid B at a uniform speed; 0.12 g of potassium sulfate was added; 0.2 g of ZSM-23 seed crystals were added; low temperature 60°C hydrothermal crystallization was performed for 6 h; 160°C crystallization was performed for 24 h, with a rotation speed of 100 rpm; the hydrothermal crystallization product was washed and dried, and then baked at 500°C for 12 h to obtain a ZSM-23 molecular sieve.
[0077] Comparative Example 5
[0078] The difference between Comparative Example 5 and Example 1 is that tetraethylenepentamine is used for modification in step (5).
[0079] The catalysts of Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to the following evaluations.
[0080] 1. Evaluation of Hexadecane Model Compounds
[0081] Catalyst evaluation was carried out in a microreactor fixed bed device. n-Hexadecane was used as the model reactant and 2 g of catalyst was loaded. The catalyst was reduced in a hydrogen atmosphere before the reaction. After the reduction was completed, the oil feed rate was 0.1 ml / min and the hydrogen flow rate was 50 ml / min. The reaction pressure was atmospheric pressure and the mass space velocity was 2.31 h -1, hydrogen to oil volume ratio 500, reaction temperature 266°C. The results are shown in Table 1. Among them,
[0082] Total conversion rate = (1 - mass fraction of n-hexadecane in the product) × 100%.
[0083] Selectivity = isohexadecane in product ÷ total conversion × 100%.
[0084] Table 1
[0085]
[0086]
[0087] 2. Evaluation of Fischer-Tropsch wax narrow fraction as raw material
[0088] The raw material is a narrow fraction of refined wax from Fischer-Tropsch synthesis (350-470°C), and the evaluation is carried out on a 100ml hydrogenation unit. Process conditions: reaction pressure 3.5MPa, mass space velocity 1h -1 , reaction temperature 333℃, hydrogen to oil ratio 500, the results are shown in Table 2.
[0089] Table 2
[0090]
[0091] As can be seen from the above, compared with Comparative Examples 1 and 2, the base oil yield of each embodiment of the present invention is significantly improved; compared with Comparative Examples 3 to 5, the base oil yield and properties of each embodiment of the present invention are significantly improved. It can be seen that the present invention uses a DMF template, and by optimizing the catalyst formula and synthesis path, a ZSM-23 molecular sieve with special pores and acidity is prepared, and then a bifunctional Pt / ZSM-23 catalyst is prepared by an equal volume impregnation method, and it is modified by an organic amine, which further increases its specific selectivity for Fischer-Tropsch wax raw materials, and the preparation method is simple and low in cost. The prepared modified catalyst has excellent isomerization performance, and is particularly suitable for the hydrogenation isomerization reaction of Fischer-Tropsch wax raw materials, so that the mass transfer of materials during the reaction process is improved, and heavy straight-chain alkanes are effectively converted, thereby preparing a high viscosity index and low pour point base oil. The modified catalyst of the present invention has high reactivity and selectivity, and can significantly improve the base oil yield. In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the yield and properties of the base oil are better.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified Pt / ZSM-23 catalyst, characterized in that: The following steps are involved: Step S1, mixing a silicon source, an aluminum source, sodium hydroxide, a DMF template, a seed crystal and water to obtain a sol; crystallizing the sol, and then performing a first calcination to obtain a Na-type ZSM-23 molecular sieve; Step S2, exchanging the Na-type ZSM-23 molecular sieve with an ammonium salt aqueous solution, and then performing a second calcination to obtain an H-type ZSM-23 molecular sieve; Step S3, mixing the H-type ZSM-23 molecular sieve with alumina, adding nitric acid for kneading, extruding into strips, and then performing a third calcination to obtain a ZSM-23 catalyst carrier; Step S4, impregnating the ZSM-23 catalyst support in a Pt salt solution, and then performing a fourth calcination to obtain a Pt / ZSM-23 catalyst; Step S5, adding organic amine and water to the Pt / ZSM-23 catalyst to modify it, and then performing a fifth calcination to obtain the modified Pt / ZSM-23 catalyst; In the step S4, the temperature of the fourth calcination is 350-450° C. and the time is 1-5 hours; In the step S5, the organic amine is n-butylamine; per gram of the Pt / ZSM-23 catalyst, the amount of water added is 5-20 g, and the amount of the organic amine added is 5-15 mmol; The temperature of the modification process is 150-200°C and the time is 15-30h; The fifth calcination is performed at a temperature of 450-550° C. and for a time of 5-10 hours.
2. The preparation method according to claim 1, characterized in that: In step S1, the silicon-aluminum ratio is (80-200):1; the mold silicon ratio is (0.5-0.8):1, the alkali silicon ratio is (0.07-0.9):1, the water silicon ratio is (20-50):1, and the crystalline silicon ratio is (0.02-0.1):
1.
3. The preparation method according to claim 2, characterized in that: The aluminum source is Al2(SO4)3·18H2O, the silicon source is silica sol, and the seed crystal is ZSM-23.
4. The preparation method according to claim 1 or 2, characterized in that: In the step S1, the crystallization temperature is 140-180° C. and the time is 24-150 hours.
5. The preparation method according to claim 4, characterized in that: The first calcination temperature is 450-600° C. and the time is 4-10 hours.
6. The preparation method according to claim 1 or 2, characterized in that: In step S2, the ammonium salt aqueous solution is an ammonium chloride aqueous solution.
7. The preparation method according to claim 6, characterized in that: The mass concentration of the ammonium salt aqueous solution is 0.2-0.8 mol / L.
8. The preparation method according to claim 7, characterized in that: The ammonium exchange is performed at a temperature of 50-90° C., for 2-4 times, and for 0.5-2 hours per exchange.
9. The preparation method according to claim 8, characterized in that: The second calcination is carried out at a temperature of 500-600° C. and for a time of 8-16 hours.
10. The preparation method according to claim 1 or 2, characterized in that: In the step S3, the mass ratio of the H-type ZSM-23 molecular sieve to the alumina is (6-8):3, and the amount of nitric acid added is 1-5% of the total mass of the H-type ZSM-23 molecular sieve and the alumina.
11. The preparation method according to claim 10, characterized in that: The third calcination is carried out at a temperature of 500-600° C. and for a time of 8-16 hours.
12. The preparation method according to claim 1 or 2, characterized in that: In the step S4, the Pt metal loading in the Pt / ZSM-23 catalyst is 0.2-0.6%.
13. The preparation method according to claim 12, characterized in that: The fourth calcination is performed at a temperature of 350-450° C. and for a time of 1-5 hours.
14. A modified Pt / ZSM-23 catalyst, characterized in that: Obtained by the preparation method according to any one of claims 1 to 13.
15. Use of the modified Pt / ZSM-23 catalyst according to claim 14 in Fischer-Tropsch wax hydroisomerization.
